KIR channel regulation of electrical conduction along cerebrovascular endothelium: Enhanced modulation during Alzheimer's disease. (6th January 2023) - Hakim, Md A.; Behringer, Erik J.
Abstract: Objective: Endothelial cell (EC) coupling occurs through gap junctions and underlies cerebral blood flow regulation governed by inward‐rectifying K + (KIR ) channels. This study addressed effects of KIR channel activity on EC coupling before and during Alzheimer's disease (AD). Methods: Intact EC tubes (width: ~90–100 μm; length: ~0.5 mm) were freshly isolated from posterior cerebral arteries of young Pre‐AD (1–3 months) and aged AD (13–18 months) male and female 3xTg‐AD mice. Dual intracellular microelectrodes applied simultaneous current injections (±0.5–3 nA) and membrane potential (Vm ) recordings in ECs at distance ~400 μm. Elevated extracellular potassium ([K + ]E ; 8–15 mmol/L; reference, 5 mmol/L) activated KIR channels. Results: Conducted Vm (∆Vm ) responses ranged from ~−30 to 30 mV in response to −3 to +3 nA (linear regression, R 2  ≥ .99) while lacking rectification for charge polarity or axial direction of spread. Conduction slope decreased ~10%–20% during 15 mmol/L [K + ]E in Pre‐AD males and AD females. 15 mmol/L [K + ]E decreased conduction by ~10%–20% at lower ∆Vm thresholds in AD animals (~±20 mV) versus Pre‐AD (~±25 mV). AD increased conducted hyperpolarization by ~10%–15% during 8–12 mmol/L [K + ]E . Conclusions: Brain endothelial KIR channel activity modulates bidirectional spread of vasoreactive signals with enhanced regulation of EC coupling during AD pathology.